The Nicher Market Strategy of BPRS Mitra Mentari in Increasing Financing for MSME Entrepreneurs - Masykuroh, Ely; Anhar, Fibrianis Puspita; Haris, Berlianto (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: Profit-sharing financing is a key feature of Islamic banks and should be maintained. One example is the Micro Express product, designed for MSMEs, especially small traders. However, BPRS faces strong competition from both conventional banks and informal lenders known as Plecit Banks. This study aims to examine the market share and competitors of the Micro Express at BPRS Mitra Mentari and to develop effective strategies to boost its financing. Research Methods: This research is field research using a qualitative approach with descriptive analysis. Results: As a market follower, BPRS can apply an imitator and adopter strategy by adopting competitor tactics—such as the pick-up service commonly used by Plecit Banks—and enhancing them through culturally unique approaches rooted in local wisdom, offering a distinct value proposition. Conclusion: Maintaining compliance with sharia principles remains essential—not only as a core identity of Islamic banks but also as a sustainable competitive advantage in the face of intense competition.